Current Development And Trends Of Sport Tourism In Uzbekistan (The Peerian Journal, 2024)
This article’s systematic review examines the most recent research on the relationship between sports tourism development and trends in a certain location. This study used a systematic literature review process with ANOVA principles. A total of 50 relevant papers were located through exhaustive database searches, with 15 articles meeting the study’s inclusion criteria. The research was examined and combined to highlight the primary economic benefits and challenges of hosting athletic events. The analysis concluded that sports tourism benefits regions by drawing tourists, offering job possibilities, and generating cash for local companies. Sports events, whether small or large, can boost regional economies.